APLIKASI METODE KERNEL DALAM ESTIMASI FUNGSI HAZARD - Priatna, Bambang Avip (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2005)
Let T be a nonnegative random variable representing the lifetimes of individuals in some population. Let f(t) denote the probability density function of T and F(t) denote the distribution function of T, the hazard function of T defined asIf equation (1) integrated we have cumulative hazard function H (t).This paper describes application of kernel method for estimation of hazard function h (.) based censoring data. And then we will show that the hazard estimator is unbiased asymptotically, consistent, and normal asymptotically.